2015
DOI: 10.1542/peds.2014-1787
|View full text |Cite
|
Sign up to set email alerts
|

Age at Gluten Introduction and Risk of Celiac Disease

Abstract: OBJECTIVES: The goal of this study was to determine whether age at introduction to gluten was associated with risk for celiac disease (CD) in genetically predisposed children. METHODS: TEDDY (The Environmental Determinants of Diabetes in the Young) is a prospective birth cohort study. Newborn infants (N = 6436) screened for high-risk HLA-genotypes for CD were followed up in Finland, Germany, Sweden, and the United States. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 26 publications
4
98
0
6
Order By: Relevance
“…However, it was unclear whether it provided long-term prevention against CD or only delayed the onset of the disease [24,[35][36][37] . Results of the recently published cohort studies did not confirm the protective effect of breastfeeding at the time of gluten introduction on developing CD [31,38] . Also, the pooled results for 7 observational studies showed that breastfeeding at the time of gluten introduction has no effect on the risk of developing CD compared with formula feeding (OR 0.88, 95% CI 0.52-1.51) [10] .…”
Section: Breastfeeding At the Time Of Gluten Introductionmentioning
confidence: 86%
“…However, it was unclear whether it provided long-term prevention against CD or only delayed the onset of the disease [24,[35][36][37] . Results of the recently published cohort studies did not confirm the protective effect of breastfeeding at the time of gluten introduction on developing CD [31,38] . Also, the pooled results for 7 observational studies showed that breastfeeding at the time of gluten introduction has no effect on the risk of developing CD compared with formula feeding (OR 0.88, 95% CI 0.52-1.51) [10] .…”
Section: Breastfeeding At the Time Of Gluten Introductionmentioning
confidence: 86%
“…[1][2][3] However, due to the plethora of unspecific gastrointestinal and extra-intestinal symptoms involved, the great majority of affected children remain unrecognized. 1,2 Since screening for the disease is simple by modern antibody tests, it has been suggested that for increased diagnostic efficiency we should screen either known at-risk groups [4][5][6] or even the whole population. 7 However, although celiac disease fulfils several WHO criteria for screening, the overall benefits of this approach remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…En una cohorte noruega (26), el inicio de ingesta de gluten después de los 6 meses se asoció a un mayor riesgo de EC, lo cual concuerda con estudios previos de Norris (18). Hasta ahora la recomendación general ha sido iniciar el gluten entre los 4 y 6 meses, preferentemente mientras el niño aún esté con lactancia materna (11,13,19,27). Hay que tomar en cuenta que estas recomendaciones se basan en un número limitado de estudios y los resultados han sido obtenidos en poblaciones de características muy distintas.…”
Section: Lactancia Materna Y Riesgo De Ecunclassified